Comparative Evaluation of Aortic Valve Replacement Methods in Patients Over 70 with Aortic Stenosis - V. V. Sokolov; M. V. Parkhomenko; A. I. Kovalyov; V. V. Vladimirov; O. L. Shiryayeva; N. M. Bikbova; V. K. Timerbayev (Неотложная медицинская помощь, 2018)
Background As life expectancy and quality of health improve, more and more people reach old age, and so does the number of heart diseases. One of the most urgent problems among elderly patients is degenerative stenosis of the aortic valve (AV). The conservative treatment of symptoms of chronic heart failure with AV stenosis improves the patient’s condition only for a while, whereas surgical treatment such as replacement of AV is recognized as the main effective method of treating a defect. Recently, alternative technologies for prosthetic AV have been developed, aimed at reducing adverse effects of artificial circulation (AC) in high-risk patients and minimizing the scope of surgical intervention.Aim of study The aim of the study was to evaluate the immediate results of surgical treatment of aortic stenosis using different methods in patients over 70.Material and methods The article presents the results of treatment of 64 patients over 70 with isolated AV stenosis, operated with different surgical techniques from July, 2016 to January, 2018. All patients were divided into three groups, differing in the severity of the initial condition and the method treatment. Group 1 (transcatheter implantation of the prosthetic AV, EuroSCORE II — 21.81%) consisted of 19 patients, Group 2 (non-suture implantation of a Perceval prosthetic valce under the AC, EuroSCORE II — 13.81%) consisted of 13 patients and Group 3 (“standard” prosthetics, EuroSCORE II — 9.89%) consisted of 32 patients.Results In Group 1, two patients died, the hospital mortality was 10.5%. In Group 2 and Group 3, one patient died, the hospital mortality was 7.6 and 3.1%, respectively. Implantation of a permanent pacemaker was required in three patients (15.7%) from the TAVI group after installation of Medtronic Core Valve and two patients (15.3%) from the Perceval group.Conclusion The obtained results of AV replacement by various methods allowed to expand indications for the management of AV stenosis in patients of the older age group with a high surgical risk of operation under AC conditions who had not previously been considered candidates for surgical treatment of aortic malformation due to the age and severity of the concomitant pathology.